Leaf-litter thrips of the genus Psalidothrips (Thysanoptera, Phlaeothripidae) from Australia, with fifteen new species - Wang, Jun; Mound, Laurence A.; Tree, Desley J. (Zootaxa, 2019)
A key is given to 16 Psalidothrips species known from Australia. In contrast to members of this genus from other parts of the world, most of these species show a strong tendency toward wing loss, with associated character states, also remarkable reduction in sclerotisation of the thoracic sclerites. Character state variation is discussed, and 15 new species are described and illustrated: P. bipictus sp.n., P. brittoni sp.n., P. cecryphalus sp.n., P. daguilari sp.n., P. driesseni sp.n., P. gloriousi sp.n., P. greensladeae sp.n., P. howei sp.n., P. minantennus sp.n., P. platetus sp.n., P. postlei sp.n., P. tritus sp.n., P. trivius sp.n., P. verus sp.n. and P. wellsae sp.n.